Geo-economic determinants of sustainable development of the state in the modern world: foreign analytics - Vanhemping, Elina G. (Journal of Economic Research & Business Administration, 2023)
The experience of foreign geo-economic research is relevant for the systematic study and identification of provisions, tools, technologies that are effective for use in modern Kazakh economic policy. In this article, the author carries out a comparative analysis of scientific and methodological approaches, strategic conclusions and key tactical recommendations presented in the modern research discourse of the leading scientific and analytical centers of Finland regarding the impact of modern geo- economic statuses of states on the processes of their sustainable development. Finland’s experience may be acceptable for Kazakhstan in different aspects. Finland has successfully developed innovative technologies, which may be of interest to Kazakhstan, which is striving for modern technological development. Kazakhstan can study Finnish experience in the field of innovation and use it to stimulate its own development. Such a comparative approach to the foreign experience of strategic geo-economic research is relevant for the vision of new reference points in understanding the place and role of Kazakhstan in modern geo-economics. Also, a systematic analysis of the foreign discourse of strategic geo-economic research presented in this article can help identify the most effective innovative technologies of public administration, the use of which will strengthen the resources of the effectiveness of research on political economic reforms and transformations in the Republic of Kazakhstan. Key words: Geo-Economics, Economic Risks, Political Economic Reforms, State Strategy, Security Concept.